Encyclopedia of Structural Health Monitoring 2008
DOI: 10.1002/9780470061626.shm029
|View full text |Cite
|
Sign up to set email alerts
|

Ship and Offshore Structures

Abstract: Structural health monitoring techniques for ship and offshore structures are summarized in this article. Owing to the increasing accidents associated with bulk carriers and large oil tankers, international regulating committees have recommended the use of hull stress monitoring systems for bulk carriers of 20 000 dwt and above to reduce the risks of structural failure since 1994. In this article, typical hull stress monitoring systems (HMS) and common sensors with monitored parameters are discussed. Long‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Kim et al [ 125 ] showed the typical general arrangement of a bulk carrier with the common location of sensors on this type of vessel.…”
Section: Monitoring Systems In Shipping and Offshore Industrymentioning
confidence: 99%
“…Kim et al [ 125 ] showed the typical general arrangement of a bulk carrier with the common location of sensors on this type of vessel.…”
Section: Monitoring Systems In Shipping and Offshore Industrymentioning
confidence: 99%